2006
DOI: 10.1108/10662240610642532
|View full text |Cite
|
Sign up to set email alerts
|

E‐mail marketing at the crossroads

Abstract: Purpose -The purpose of this paper is to provide a conceptual overview of the process of unsolicited commercial e-mail (UCE), propose a typology of UCE, and delineate key stakeholders of UCE, their roles and potential responses through a stakeholder analysis. Design/methodology/approach -Based on the extant literature, this paper provides a conceptualization of the UCE process, delineating specific types of UCE. It uses stakeholder analysis to identify key members in the UCE process and the potential roles to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…One study found that 52% of consumers shopped less on the Internet or stopped altogether as a result of concerns relating to SPAM (Gratton, 2004). In short, SPAM poses a fundamental threat to the growth of e-commerce (Moustakas et al, 2006). This raises the question; if SPAM serves as such a threat to online shopping, how can email continue to serve as a key marketing communication tool?…”
Section: The Relationship Between Email Marketing Spam and Permission Email Marketingmentioning
confidence: 99%
“…One study found that 52% of consumers shopped less on the Internet or stopped altogether as a result of concerns relating to SPAM (Gratton, 2004). In short, SPAM poses a fundamental threat to the growth of e-commerce (Moustakas et al, 2006). This raises the question; if SPAM serves as such a threat to online shopping, how can email continue to serve as a key marketing communication tool?…”
Section: The Relationship Between Email Marketing Spam and Permission Email Marketingmentioning
confidence: 99%
“…However, other ways seem to be promising, such as guidelines for companies to restrict uncontrolled electronic marketing, especially taking into account business reputation (the fear of having a bad business reputation, it is especially effective in Asian countries). Legislation in this regard is most effective as a deterrent than threatening with large fines and prison penalties (Moustakas et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Email marketing is an important medium of marketing communication especially for companies seeking to build and maintain closer relationships with customers (McCloskey, 2006). Widespread adoption of e-mail as a means of distributing promotional messages has the advantages of low setup and distribution costs, targeted distribution of promotions such as discounts and coupons, and affordability by small and medium-sized businesses (Moustakas, Ranganathan, and Duquenoy, 2006).…”
Section: Email Marketingmentioning
confidence: 99%